A simple method of fabrication hybrid electrodes for supercapacitors - Samaneh Mahmoudi-Qashqay; Mohammad-Reza Zamani-Meymian; Ali Maleki (Scientific Reports)
Abstract The increasing need for electrode materials exhibiting improved performance to meet the requirements of supercapacitors is on the rise. Hybrid electrodes, which combine reduced graphene oxide (rGO) with transition metal-based oxides, have emerged as promising materials due to their impressive specific capacitance and cost-effectiveness, attributed to their synergistic properties. In the present study, a binder-free CoOrGO composite electrode was synthesized using a facile, fast, and simple one-step co-precipitation method. This was done to improve both capacity and stability for supercapacitor applications. The composite materials underwent comprehensive characterization utilizing various surface analytical techniques, including X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), field-emission scanning electron microscopy (FE-SEM), fourier-transform infrared spectroscopy (FTIR), and Brunauer–Emmett–Teller (BET) analysis. Electrochemical measurements of the CoOrGO composite revealed at current density of 2 A cm− 2 a specific capacitance of 132.3 mF cm− 2, with an impressive 95.91% retention of capacitance after 7000 cycles. The results from electrochemical impedance spectroscopy (EIS) highlighted a meager low relaxation time constant of 0.53 s for the composite films. The reason behind this can be linked to the synergistic interactions, and minimal charge transfer resistance exhibited by the porous electrode without binders. Based on the obtained results, this work introduces a flexible methodology for crafting advanced energy storage systems. This demonstrates the potential for designing high-efficiency supercapacitors that are suitable for a broad range of large-scale applications.